Be Sweet to Hospitalized Toddlers During Venipuncture: A Randomized Controlled Trial of Sucrose Compared With Water. Issue 1 (January 2022) - Modanloo, Shokoufeh; Barrowman, Nick; Martelli, Brenda; Yoxon, Helen; Wilding, Jodi; Dragic, Sandra; Vaillancourt, Régis; Long, Deborah; Larocque, Catherine; Reszel, Jessica; Harrison, Denise
Abstract : Objectives: High-quality evidence demonstrates analgesic effects of sweet-tasting solutions for infants during painful procedures. However, evidence of the analgesic effects of sucrose beyond 12 months of age is less certain. The aim of this study was to ascertain the efficacy of oral sucrose in hospitalized toddlers (ages 12 to 36 mo) compared with placebo (water) during venipuncture. Materials and Methods: Blinded, 2-armed randomized controlled trial including hospitalized toddlers aged 12 to 36 months. Toddlers were randomized to either 25% sucrose or water before venipuncture, stratified by age (12 to 24 mo and more than 24 to 36 mo). Standard of care included topical anesthetics for both groups. Pain assessment included cry duration and FLACC (Face, Legs, Activity, Cry, Consolability) scores. Descriptive statistics and linear models were used to report the percentage of time crying and mean differences in FLACC scores. Data analysis was performed using R, version 3.6.3. Results: A total of 95 toddlers were randomized and 85 subsequently studied. The median percentage of time spent crying between insertion of the first needle and 30 seconds after the end of procedure in both groups was 81% (interquartile range=66%). There was no significant difference in crying time and FLACC scores between groups ( P >0.05). When examining effects of sucrose for the younger toddlers (less than 24 mo of age) there was a reduction in crying time of 10% and a 1.2-point reduction in mean FLACC scores compared with the toddlers older than 24 months. Discussion: Findings highlight that toddlers become highly distressed during venipuncture, despite the standard care of topical anesthetics. In addition, sucrose does not effectively reduce distress especially in the older group of toddlers.